Quality of Stroke Patient Information Applied in Randomized Controlled Trials—Literature Review - Alegiani, Anna C.; Rahn, Anne C.; Steckelberg, Anke; Thomalla, Götz; Heesen, Christoph; Köpke, Sascha (Frontiers in Neurology, 2020)
Background Stroke has a huge impact on patients` quality of life. Although, there are potentially effective secondary prevention options, adherence is mostly low. Lack of disease and treatment related knowledge and consequently lack of informed choice in stroke patients may contribute to this problem. However, information interventions have mostly shown disappointing results. One contributing factor may be the lack of thoroughly developed patient information materials. Methods We aimed to evaluate the quality of patient information materials for stroke patients applied in randomized-controlled trials using criteria for evidence based patient information (EBPI). Therefore, we conducted a systematic literature review based on the inclusion criteria of a Cochrane Review. Authors of primary studies were contacted and asked for information materials applied. Results We identified 30 eligible studies. Information materials were available for only eight studies. The analysis revealed that all available materials had important shortcomings concerning criteria for EBPI: as e.g. no comprehensive description of treatment effects (n=7) and side effects (n=8). Frequently, treatment effects were reported only narratively without providing absolute numbers, values or frequencies. Conclusion Quality of materials differed, but none sufficiently fulfilled criteria for evidence based patient information. Unsatisfactory trial results concerning patient knowledge and patient involvement may at least partially be explained by limitations of the provided materials.